iPro user : a case study of pro-am photographers in Malaysia travel magazine - Teh, Chree Yee (2012)
In the digital era, centralized media is moving towards de-centralized and globalized network. This development changes the relationship between mass media and their audiences, remodels the connection among media users and expands traditional roles of consumers. Consumer behavior changes blur the distinction between producer-consumer, professional-amateur, and work-leisure. With a title of ‘iPro User’ which refers to ‘I am a productive and professional user’, this paper is applying ‘pro-am’ model with a framework of ‘prosumer’ to investigate why and how a group of professional amateurs are networked together and utilize digital devices to participate as content contributors. This prosumption phenomenon is examined with a single case study in Malaysia travel magazine – Travelmate. Empirical data are gathered through in-depth interviews with magazine editors and non-professional photographers who actively contribute in imagery content production. Findings indicate that Travelmate has been functioning as a participatory platform for pro-am photographers to engage as prosumers. Pro-am identity was constructed during prosumption process whereby strong personalities and unique ethos are developed. Pro-ams portray complex behaviors, as their non-financial pursuit via vested interest and commitment creates knowledge and social distinction from non-serious hobbyists. They serve as marginal ethnics who balance social contradiction between wage and free labors, skilled and inexperienced players, unserious and innovative workers.